2009
DOI: 10.1002/hep.22987
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the hepatitis C virus polymerase that increase RNA binding can confer resistance to cyclosporine A

Abstract: Hepatitis C virus (HCV) infection leads to acute and chronic liver diseases, and new classes of anti-HCV therapeutics are needed. Cyclosporine A (CsA) inhibits HCV replication and CsA derivatives that lack the immunosuppressive function are currently in clinical trials as candidate anti-HCV drugs. Here we characterize several independently derived HCV replicons with varying levels of CsA resistance due to mutations in nonstructural protein 5B (NS5B), the HCV-encoded polymerase. Mutant HCV replicons engineered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
3
24
3
Order By: Relevance
“…We examined ⌬21 ( Fig. 2A) along with several mutant derivatives that are affected for oligomerization (E18R mutant [46]), de novo initiation (m26-30 and I432V mutants [10,27]), or in the GTPbinding allosteric site (P495/V499A mutant, named PV [6]) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined ⌬21 ( Fig. 2A) along with several mutant derivatives that are affected for oligomerization (E18R mutant [46]), de novo initiation (m26-30 and I432V mutants [10,27]), or in the GTPbinding allosteric site (P495/V499A mutant, named PV [6]) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we analyzed several other mutant RdRps and found that the I432V mutant was a good choice for reconstruction. The I432V substitution was originally identified in a mutant HCV replicon that was resistant to cyclosporin A and subsequently was shown to be better at de novo initiation than the wild-type (WT) ⌬21 protein, especially at higher enzyme concentrations (27) (Fig. 9A and B).…”
Section: Vol 84 2010mentioning
confidence: 99%
“…It would be interesting to systematically determine whether any additional NS5A interactions, especially the ones that involve domains II and III, are dependent on CyPA's PPIase activity and thus sensitive to CPIs. CyPA has also been proposed to regulate NS5A/5B cleavage kinetics (27) and/or RNA binding by HCV replicase (17,33). Although domain I is likely the major RNA-binding domain of NS5A and some controversies currently surround whether domains II and III are directly involved in NS5A's RNA-binding ability or not (16,25), it is theoretically possible for structural changes in domain II and LCS-II to influence the configuration of domain I dimers.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of CyPA's PPIase activity in HCV replication has been confirmed by several independent labs using both chemical and RNA interference approaches (5, 27, 34), but the relevant substrates of the PPIases are much less defined. At least three HCV proteins (NS2, NS5A, and NS5B) have been implicated in the action of CyPA as an HCV cofactor (7,21,33), and increasing evidence supports a direct interaction between CyPA and NS5A (8,14,21,58,63). Recombinant CyPA protein interacts with both full-length NS5A from infected cell lysates and purified NS5A domains.…”
mentioning
confidence: 99%
“…A-782759 selects highly fit mutations at NS5B residue M414 that confer a large decrease in drug susceptibility (17,18). In contrast, a single HCV mutation that confers a more than fivefold shift in potency has not been reported despite a large body of literature on CsA (19)(20)(21). When a large (10 5 ) population of 51C-RFP-1a replicon cells was treated with each of these drugs, a dramatic difference in the frequency of resistance foci was observed (Fig.…”
Section: Quantification Of Relative Frequencies Of Preexisting Drug-rmentioning
confidence: 99%